Consumers and Consumerism - Subramanium, Melarkode P. (Indian Journal of Marketing, 2004)
The Market that we experience today is not only a changed market but also a fast changing market. If Alice (yes, the same little girl in "Alice in Wonderland").Were to be in the present day market; looking at the countless volume and variety of products and services produced, purchased and consumed, stiff competition among the producers, marketers and consumers, she would have definitely cried again, "Curiouser And Curioser". For a student of marketing, it will be an interesting and educative proposition to look at how the consumers have placed and positioned themselves in the marketing environment that they are in.